Determinants of Students’ Achievement in Arabic Syntax at Universiti Teknologi MARA (Shah Alam), Malaysia - Audia Syawwalina, Dyah; Talqis Nurdianto; Ana Taqwa Wati; Lutfi Hassan (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2025)
This study aimed to analyze the influence of internal and external factors on students’ cumulative achievement index (CGPA) in the Nahwu course at Universiti Teknologi MARA (Shah Alam), Malaysia. Employing a quantitative descriptive approach, data were collected from 58 students of the Arabic Language for Professional Communication program using questionnaires and academic documentation. Multiple linear regression analysis was conducted using SPSS 25 to examine the relationships among variables. The results indicate that internal and external factors are jointly associated with students’ CGPA, although their simultaneous contribution is relatively low. Partially, internal factors show a positive but insignificant effect, while external factors demonstrate a negative and insignificant influence on CGPA. These findings suggest that students’ achievement in Nahwu is influenced by a complex interaction of academic, psychological, and pedagogical dimensions beyond the examined variables. In conclusion, improving Nahwu learning outcomes requires integrative instructional strategies that address both internal student characteristics and the external learning environment.